ANALYSIS OF THE MEANINGS OF AḤWᾹL MUTTAʻALIQᾹT AL-FIʻLI BASED ON RELEVENCE THEORY IN SURAH AL-MULK - Nur Hasanah, Marliana; Syihabuddin; Nalahuddin Saleh (Lahjah Arabiyah: Jurnal Bahasa Arab dan Pendidikan Bahasa Arab, 2024)
Linguistic structure greatly influences the understanding of the meaning of an utterance. However, in contrast to general discourse, the linguistic structure of the Qur'anic language style has a rich and deep meaning. One of the language styles that has an unusual construct is ahwal mutaʽalliqāt al-fiʽli. Relevance theory is present to reveal the meaning of ahwal mutaʽalliqāt al-fiʽli contained in the verses of the Qur'an so that it becomes evidence to strengthen the miracle of the Qur'an in terms of its language. This research aims to introduce as well as focus on examining more deeply the meanings of ahwal mutta'alliqat al'fi'li in the verses of the Qur'an. The research method used is descriptive-interpretative with Content Analysis model. The approach used is an inductive approach which is then presented descriptively to explain the meaning of ahwal mutaʽalliqāt al-fiʽli based on the principles of relevance theory formulated by Sperber and Wilson. The findings obtained a total of 16 data of ahwal mutaʽalliqāt al-fiʽli from 11 verses of surah al-Mulk which are divided into the categories of omitting fāʽil, omitting maf'ul, giving precedence to maf'ul, giving precedence to jār majrūr, and giving precedence to żaraf. All data are understood by contextual reasoning based on the theory of relevance which is also in line with the rules of balaghah according to Al-Harbi and Al-Hasyimi.